Senyawa Antiinflamasi dari Fraksi Etil Asetat Akar Pandan Wangi (Pandanus amaryllifolius Roxb.) Terhadap Udema Kaki Mencit Terinduksi Karagenan - Diva Feraldy; Endah Sayekti; Ari Widiyantoro (Jurnal Fitofarmaka Indonesia, 2023)
Inflammation can occur due to insect bites, toxins, burns and blows. Inflammation can be cured using Non-Steroid Anti-Inflammatory Drugs (OIANS). Fragrant pandan root is thought to have anti-inflammatory activity because it contains alkaloids and flavonoid compounds. This study aims to determine the activity and characteristics of anti-inflammatory compounds from extracts, fractions and isolates of ethyl acetate root of fragrant pandan (Pandanus amaryllifolius Roxb.) against carrageenan-induced foot edema of mice. The process of isolation of fragrant pandan roots includes stages such as maceration, partitioning and chromatography. The results of the study The methanol extract had good activity at a dose of 200 mg/kg BB for a period of time (t3) 51.7%; the methanol fraction had good activity at a dose of 200 mg/kg BB in the time span (t3) 38.2%; the ethyl acetate fraction had good activity at a dose of 200 mg/kg BB over a period of time (t3) 56.9%; the dichloromethane fraction had good activity at a dose of 200 mg/kg BB in the time range (t3) 59.2%; the n-Hexane fraction had good activity at a dose of 200 mg/kg BB for a period of time (t3) 37.1%; and isolates had good activity at a dose of 50 mg/kg BB over a period of time (t3) 35.6%. K2 isolate from the ethyl acetate fraction was characterized using 1H-NMR with DMSO solvent at a frequency of 500 MHz and 13C-NMR with DMSO solvent at a frequency of 125 MHz. K2 isolate from the ethyl acetate fraction had similarities to Pandalisines A.